Volatile threshold switching and synaptic properties controlled by Ag diffusion using Schottky defects - Jeon, Yu-Rim; Akinwande, Deji; Choi, Changhwan (Nanoscale horizons, 2024)
We investigated diffusion memristors in the structure of Ag/Ta 2 O 5 /HfO 2 /Pt, in which active Ag ions control active metal ion diffusion and mimic biological brain functions. The CMOS compatible high- k metal oxide could control an Ag electrode that was ionized by applying an appropriate voltage to form a conductive filament, and the movement of Ag ions was chemically and electrically controlled due to oxygen density. This diffusion memristor exhibited diffused characteristics with a selectivity of 109, and achieved a low power consumption of 2 mW at a SET voltage of 0.2 V. The threshold transitions were reliably repeatable over 20 cycles for compliance currents of 10 −6 A, 10 −4 A, and no compliance current, with the largest standard deviation value of SET variation being 0.028. Upon filament formation, Ag ions readily diffused into the interface of the Ta 2 O 5 and HfO 2 layer, which was verified by investigating the Ag atomic percentage using XPS and vertical EDX and by measuring the relaxation time of 0.8 ms. Verified volatile switching device demonstrated the biological synaptic properties of quantum conductance, short-term memory, and long-term memory due to controlling the Ag. Diffusion memristors using designed control and switching layers as following film density and oxygen vacancy have improved results as low-power devices and neuromorphic devices compared to other diffusion-based devices, and these properties can be used for various applications such as selectors, synapses, and neuromorphic devices. The identified mechanism of the high- k metal oxide by XPS, XRR, and TEM applied to a synaptic device as a diffusion memristor with control and switching layers that could control Ag ion migration, emulating the synaptic plasticity.